Parallel Viterbi algorithm implementation: breaking the ACS-bottleneck - Fettweis, G.; Meyr, H. (IEEE transactions on communications, 1989)
The central unit of a Viterbi decoder is a data-dependent feedback loop which performs an add-compare-select (ACS) operation. This nonlinear recursion is the only bottleneck for a high-speed parallel implementation. A linear scale solution (architecture) is presented which allows the implementation of the Viterbi algorithm (VA) despite the fact that it contains a data-dependent decision feedback loop. For a fixed processing speed it allows a linear speedup in the throughput rate by a linear increase in hardware complexity. A systolic array implementation is discussed for the add-compare-select unit of the VA. The implementation of the survivor memory is considered. The method for implementing the algorithm is based on its underlying finite state feature. Thus, it is possible to transfer this method to other types of algorithms which contain a data-dependent feedback loop and have a finite state property.< >